Editor's Choice – A Comparison of Computed Tomography Angiography and Colour Duplex Ultrasound Surveillance Post Infrarenal Endovascular Aortic Aneurysm Repair: Financial Implications and Impact of Different International Surveillance Guidelines. (August 2021) - Smith, Luke; Thomas, Nicholas; Arnold, Andrew; Bell, Rachel; Zayed, Hany; Tyrrell, Mark; Padayachee, Soundrie
Abstract : Objective: Use of colour duplex ultrasound (CDUS) and computed tomography angiography (CTA) for infrarenal endovascular aortic aneurysm repair (EVAR) surveillance differs in internationally published guidelines. This study aimed firstly to compare CDUS detection of significant sac abnormalities with CTA. Secondly, a sensitivity analysis was conducted to compare financial estimates of the, predominantly CDUS based, local and Society of Vascular Surgery (SVS) protocols, the risk stratified European Society of Vascular Surgery (ESVS) protocol, and the CTA based National Institute of Health and Care Excellence (NICE) protocol. Methods: Agreement between CDUS and CTA was assessed for detection of significant sac abnormalities. Surveillance protocols were extrapolated from published guidelines and applied to infrarenal EVAR patients active on local surveillance at a large, single centre. Surveillance intensity was dependent on presence of endoleak and subsequent risk of treatment failure in accordance with surveillance recommendations. Estimates for each surveillance protocol were inclusive of a range of published incidences of endoleak, contrast associated acute kidney injury (AKI), and excess hospital bed days, and estimated for a hypothetical five year surveillance period. Results: The kappa coefficient between CDUS and CTA for detecting sac abnormalities was 0.68. Maximum five year surveillance cost estimates for the 289 active EVAR patients were £272 359 for SVS, £230 708 for ESVS, £643 802 for NICE, and £266 777 for local protocols, or £1 270, £1 076, £3 003, and £1 244 per patient. Differences in endoleak incidence accounted for a 1.1 to 1.4 fold increase in costs. AKI incidence accounted for a 3.3 to 6.2 fold increase in costs. Conclusion: A combined CTA and CDUS EVAR surveillance protocol, with CTA reserved for early seal assessment and confirmatory purposes, provides an economical approach without compromising detection of sac abnormalities. AKI, as opposed to direct imaging costs, accounted for the largest differences in surveillance cost estimates.